Telemedicine for Monitoring Nutritional Intake in Malnourished Community-Dwelling Elderly: A Scoping Review of Clinical Trials - Bryanna Infinita L. Saputro; Muhammad Ilham Dhiya Rakasiwi; Astrid Mariam KhairaniSiregar (Indonesian Journal of Human Nutrition, 2023)
Malnutrition is part of the geriatric giant and a major concern among community-dwelling elderly individuals. Improper intervention of this problem can have detrimental effects on the elderly. Monitoring nutritional intake plays a vital role in managing malnutrition. Telemedicine has been widely applied for managing chronic diseases and gained prominence during the COVID-19 pandemic as a remote health monitoring method. This scoping review aims to identify the advantages and limitations of implementing telemedicine for addressing malnutrition in community-dwelling elderly. This study reviewed the literature obtained through a systematic search of PubMed and ScienceDirect databases, supplemented by manual searches based on specific inclusion criteria.  Two randomized controlled trials (RCTs) assessing the application of telemedicine for malnutrition were identified. The forms of telemedicine used were telecare and set-top boxes on television. The interventions included nutritional monitoring and specific interventions for each patient. However, high patient dropout rates indicated low patient compliance. Nevertheless, the application of telemedicine demonstrated improved patient compliance with nutritional intake guidelines. Limitations of telemedicine implementation included low motivation, technological constraints, and physiological constraints. Telemedicine may be used as a tool for monitoring nutritional intake among malnourished geriatric populations.